A Wireless Sensory Feedback Device for Real-Time Gait Feedback and Training - Redd, C. B.; Bamberg, S. J. M. (IEEE/ASME transactions on mechatronics, 2012)
This paper presents a new sensing and feedback system for a personal gait rehabilitation device based on wireless transmission of ambulation data for real-time sensory feedback for assistive healthcare. An integrated force-sensing insole was designed, using embedded force sensitive resistors that were sampled using a microprocessor, which then transmitted the data to an Android smartphone for presentation to the user. Experiments were performed to verify that the device captured accurate gait data, and was able to influence the gait of the subject. In addition, different sensory methods of feedback were tested to determine their individual efficacy at modulating the gait of study subject. The results show that the feedback system is capable of influencing the gait of the user, without the need for direct supervision by a rehabilitation specialist. In addition, a statistical analysis was performed to establish the reliability and repeatability of the system. From these results, this feedback system is established as a novel, inexpensive, and effective candidate for use in clinical rehabilitation of persons with gait abnormalities.